The Effect of Blend-Learning on Basic Electrical and Electronics Subject in New Normal Period - Irma Rahmada Shinta; Oriza Candra (Universitas Negeri Padang, 2021)
This research is motivated by student learning outcomes in the basic electricity and electronics learning process which is not as expected. Therefore, an active and innovative learning model is needed. The research method used is the experimental method, using the one-group posttest design. In the experimental class, the Blended Learning model was treated. For the sample used in the study, the students of class X TITL at SMK Negeri 1 Bukittinggi. . Learning outcomes assessment instruments use cognitive tests and the distribution of effective questionnaires. The results of the study prove that the Blended Learning learning model can effectively improve student learning outcomes as evidenced by student learning outcomes that have reached the minimum completeness criteria (KKM) of 83.42 and from affective or attitude assessments with a percentage of 64.03% in good categories in subjects Basic Electricity and Electronics, especially in the material Analyzing power and electrical energy